ЗАКОНОМЕРНОСТИ ИЗМЕНЕНИЯ ПОТЕРЬ ЭНЕРГИИ В RL–ЦЕПЯХ, СОЕДИНЯЮЩИХ КОНДЕНСАТОРЫ, ЗАРЯЖЕННЫЕ ДО РАЗНЫХ НАПРЯЖЕНИЙ - Супруновская, Н.И.; Щерба, А.А. (Інститут електродинаміки НАН України, Київ, 2015)
It is determined that losses of the electric power and coefficient of energy transfer between two capacitors charged to different voltage and connected through RL–circuit with bidirectional commutator (conducting a current in both directions) are defined only by a difference of initial voltage on capacitors and a ratio of their capacities, and do not depend on magnitudes R and L. In this case the power interchange between capacitors is carried out until transient attenuation. At the same time it is shown that if RL–circuit is connected to capacitors by unidirectional commutator and there will be an oscillatory process of a power interchange then an energy loss will decrease, and the energy transfer coefficient will be increase at decrease of a difference of initial voltage of capacitors and with increase in inductance L. For such energy interchange the dependences of energy loss and energy transfer coefficient between capacitors from a ratio of their capacities are determined. It is shown that the greatest energy loss appears at equal capacities of connected capacitors for any values of inductance. References 14, figures 3, table 1.